Gamification in Education: Enhancing Leadership Skills among Entrepreneurship Students - Hendarsyah Aditya Saptari; Jann Hidajat Tjakraatmadja; Donald Crestofel Lantu (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2024)
In the rapidly changing world of entrepreneurship, where innovation and adaptability are paramount, traditional paradigms of education increasingly fail to equip students with the necessary leadership skills to navigate and succeed in complex business environments. This paper examines the impact of gamification on enhancing leadership skills among entrepreneurship students by employing a systematic literature review to sift through 5612 articles, ultimately focusing on 78 that met stringent criteria for relevance and quality. The methodology highlighted an extensive analysis across various educational and professional settings, illustrating gamification's effectiveness in boosting engagement, motivation, learning outcomes, and the acquisition of leadership competencies. Studies within the scope from 2019 to 2024 demonstrated gamification’s role in transcending traditional educational methods, thereby enriching the learning experience and preparing students for practical leadership challenges in entrepreneurship. The findings suggest that gamification not only enhances educational engagement and outcomes but also plays a crucial role in skill development, particularly those pertinent to leadership in an entrepreneurial context. Themes such as user experience, social and behavioral change, technology integration, and contextual adaptation have emerged as critical to the success of gamified learning approaches. By linking theoretical knowledge with practical application, gamification presents a promising avenue for developing the next generation of entrepreneurial leaders. This study significantly contributes to the theoretical framework on educational gamification by empirically demonstrating how ramified elements can effectively bridge the gap between theoretical leadership concepts and their practical application in real-world entrepreneurial scenarios, thereby providing a robust foundation for future research and practice in educational design and leadership development.